Sex differences in health and mortality by income and income changes. Issue 3 (16th December 2019) - Ahrenfeldt, Linda Juel; Pedersen, Jacob Krabbe; Thinggaard, Mikael; Christensen, Kaare; Lindahl-Jacobsen, Rune
Abstract : Background: The adverse association between income, health and survival is well documented, but little is known about how income trajectories influence health and survival for men and women. We aim to investigate sex differences in mortality and hospitalisations by income and income changes. Methods: We performed a population-based, nationwide study including 1 063 787 Danes born 1935–1955 and residing in Denmark during 1980–2015. Income was calculated during two age intervals: 45–49 and 55–59 years. The average income was divided into quartiles for men and women separately, which formed the basis for the income trajectories. Individuals were followed up from age 60 until 2014/2015 for hospital admission and mortality, respectively. Results: Men had higher mortality and were more hospitalised than women. Sex differences in mortality were most pronounced for people with stable low income (relative difference in hazard=1.93; 95% CI 1.89 to 1.98) and a downward income trajectory (1.91; 95% CI 1.85 to 1.98) with smaller sex differences for people with an upward trajectory (1.59; 95% CI 1.56 to 1.62) and stable high income (1.37; 95% CI 1.33 to 1.41). A similar pattern was found for family income. Regarding hospitalisations, similar results were found, though less pronounced. Investigation of mortality and hospitalisations by all possible trajectories demonstrated that income at ages 55–59 was an important predictor of mortality, with increasing mortality for decreasing income quartile. Conclusion: Income trajectories as a proxy for change in social position have a larger influence on men's than women's health and mortality. Income in the late 50s is an important predictor of mortality, particularly for men.